Handbook of multiphase flow assurance - Makogon, Taras Y. (Gulf Professional Publishing, an imprint of Elsevier, 2019)
Handbook of Multiphase Flow Assurance allows readers to progress in their understanding of basic phenomena and complex operating challenges. The book starts with the fundamentals, but then goes on to discuss phase behavior, fluid sampling, fluid flow properties and fluid characterization. It also covers flow assurance impedance, deliverability, stability and integrity issues, as well as hydraulic, thermal and risk analysis. The inclusion of case studies and references helps provide an industrial focus and practical application that makes the book a novel resource for flow assurance management and an introductory reference for engineers just entering the field of flow assurance.
Includes index.
Keywords: Multiphase flow -- Handbooks, manuals, etc.; elektronické knihy; electronic books